Forks in the Road: Energy Policies in Canada and the US since the Shale Revolution. Issue 1 (2nd January 2020) - Rioux, Jean-Sébastien; Winter, Jennifer
ABSTRACT: This article examines policy responses in Canada and the US to the shale revolution and changing North American oil and gas markets. We outline the effect of the shale revolution on North American oil and gas markets, and how the subsequent energy policy choices in each country changed the relationship between Canada and the US. In the US, increasing production, combined with the policy imperative of maintaining energy security, led to less support for Canadian supply and the subsequent on-off-on saga of the Keystone XL pipeline. In Canada, growing concern about the balance between the environment and the economy led to stalled pipeline development and reform of regulatory systems, problems exacerbated by the new policy direction in the US.